2015
DOI: 10.1210/me.2015-1184
|View full text |Cite
|
Sign up to set email alerts
|

HDAC5-mTORC1 Interaction in Differential Regulation of Ghrelin and Nucleobindin 2 (NUCB2)/Nesfatin-1

Abstract: Sodium valporate (VPA), a broad-spectrum inhibitor of histone deacetylases (HDACs), increased ghrelin whereas decreased nesfatin-1 in mice fed normal chow diet or high-fat diet. Alterations in ghrelin and nucleobindin 2/nesfatin-1 were mediated by HDAC5 but not HDAC4. Activation of mTORC1 significantly attenuated the effect of VPA on ghrelin and nesfatin-1 levels. HDAC5 coimmunoprecipitated with raptor. Inhibition of HDAC5 by VPA, trichostatin A, or siHDAC5 markedly increased acetylation of raptor Lys840 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The exact mechanism by which HDAC5 AA activates the mTOR pathway in RGC remains to be elucidated. There is evidence in a hypothalamic cell line that HDAC5 interacts and deacetylates Raptor, thereby activating mTOR (Ma et al, 2015). A similar mechanism might be taking place in RGCs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The exact mechanism by which HDAC5 AA activates the mTOR pathway in RGC remains to be elucidated. There is evidence in a hypothalamic cell line that HDAC5 interacts and deacetylates Raptor, thereby activating mTOR (Ma et al, 2015). A similar mechanism might be taking place in RGCs.…”
Section: Discussionmentioning
confidence: 95%
“…In RGC, these manipulations not only promote optic nerve regeneration but also RGC survival, by blocking the injury-induced dephosphorylation of the S6 ribosomal protein (S6) after optic nerve crush (Park et al, 2008). Since it has recently shown that, in a hypothalamic cell line, cytoplasmic HDAC5 can indirectly regulate mTOR activation (Ma et al, 2015), we tested if HDAC5 AA activates the mTOR pathway to promote RGC survival and regeneration. We observed a 10% increase in the number of surviving RGCs (labeled with the nuclear marker Brn3a) after injury in retinas overexpressing HDAC5 AA compared to the other treatments (One-way ANOVA F(2, 12)= 13.38, p=0.00089 with Tukey's post hoc test; p=0.004 vs GFP and p=0.001 vs HDAC5 DAD but not difference (p=0.75) between HDAC5 DAD and GFP) ( Figure 3D and E).…”
Section: Hdac5 Aa Activates Mtor and Increases Optic Nerve Regeneratimentioning
confidence: 99%
“…Because ghrelin is known for its orexigenic and lipogenic effects, and is regulated by mTOR and its downstream molecular, ribosomal protein S6 kinase beta‐1 (S6K1) (Supporting Fig. ), we hypothesized that mTOR signaling in X/A‐like cell affects organism‐level metabolism by manipulating ghrelin production.…”
Section: Resultsmentioning
confidence: 99%
“…Production of ghrelin from gastric X/A‐like cells is tightly linked with organism energy supply . Studies using the pharmacological approach suggest that gastric mTOR may serve as a critical molecule mediating the effect of energy supply on the production of ghrelin .…”
mentioning
confidence: 99%
“…HDAC5 has been shown to co-precipitates with regulatory-associated protein of mTOR (Raptor); HDAC5 inhibition promotes Raptor acetylation, subsequently inhibiting mTORC1 signaling 57 . Conversely, P13K/Akt/mTOR regulates HDAC3 phosphorylation, promoting its activity 58 .…”
Section: Discussionmentioning
confidence: 99%